N-TiO2/FeMIL-88B- A Promising Photocatalyst for Photoconversion of CO2 into Methanol - Lan, Phung Thi; Hao, Nguyen Hoang; Thuc, Nguyen Van; Ha, Nguyen Ngoc; Cam, Le Minh; Ha, Nguyen Thi Thu (VNU Journal of Science: Natural Sciences and Technology, 2023)
The present objective of this work is to find photoactive materials capable of facilitating visible light-driven redox reactions between CO 2 and H 2 O. Our research is primarily focused on the incorporation of nitrogen (N) into the crystal lattice of titanium dioxide (TiO 2 ) and its deposition onto Fe-MIL-88B to improve light absorption properties, minimize recombination of photo-generated electron-hole pairs, and increase CO 2 adsorption capacity. The N-TiO 2 /Fe-MIL-88B composite was successfully prepared and characterized using SEM, XRD, and EDX techniques. The introduction of N-TiO 2 into Fe-MIL-88B does not damage the crystal structure of Fe-MIL-88B.  Anatase is the only crystalline phase observed from the XRD diffraction pattern. SEM images show that N-TiO 2 is well dispersed on the Fe-MIL-88B surface. The results of quantum simulations indicate that TiO 2 strongly interacts with Fe-MIL-88B. The binding energy is determined to be -78.2 kcal/mol. The calculated UV-Vis results revealed that the light absorption edge of the TiO 2 /Fe-MIL-88B was red-shifted in comparison with that of the pure TiO 2 (from ca. 500 nm to 550 nm). The red-shifted light absorption of TiO 2 /FeMIL-88B suggests that the band gap of TiO 2 /Fe-MIL-88B is narrower compared to that of the pristine TiO 2 , indicating the better light utilization ability of the TiO 2 /Fe-MIL-88B. Results from high-performance liquid chromatography show that N-TiO 2 has the capability to convert CO 2 , but at a significantly low rate. The methanol formation is distinctly observed only over the N-TiO 2 /Fe-MIL-88B catalyst. The CO 2 conversion efficiency, estimated using gas chromatography, is calculated to be 11.94%.